Pore water chemistry of the Mariana serpentinite mud volcanoes: A window to the seismogenic zone - Hulme, S M; Wheat, C G; Fryer, P; Mottl, M J (Geochemistry, Geophysics, Geosystems, 2010)
In 2003, we conducted a survey of 11 serpentinite mud volcanoes in the Mariana fore arc. Here we report sediment pore water data from navigated gravity and piston cores and from push cores collected by the ROV system Jason2-Medea. Systematic variations in profiles of pore water chemical compositions from these mud volcanoes are consistent with models that include active upflow of pore water relative to the surrounding serpentinite matrix. The speed of upwelling, based on fits of an advection-diffusion model to observed data (K, Na, Rb, and Cs), reaches a maximum of 36 cm/yr at Big Blue Seamount. Results from these simulations constrain the pore water composition at depth and the degree of additional alteration as the pore water ascends through the sampled section. For example, the transition metals (e.g., Mn, Fe, Co, Ni, Cu, and Mo) are mobilized under conditions of low upwelling speeds and microbial activity. Similarly, the rare earth elements (REE) show evidence of near-surface alteration. In addition to these surficial reactions, distinctive pore water compositional patterns exist as a function of the distance from the trench axis, which is a proxy for the depths of water generation from the downgoing plate below each seamount. Systematic trends in the chemical composition of these slab-sourced fluids are consistent with increasing temperature and pressure at depth west of the trench. These trends include an increase in K, sulfate, carbonate alkalinity, Na/Cl, B, Mn, Fe, Co, Rb, Cs, Gd/Tb, Eu, and light REE (LREE) and a decrease in Ca, Sr, and Y with increasing distance from the trench. Mg and U are universally depleted in the upwelling water. We constrain the thermal conditions along the décollement using concentrations of fluid mobile elements (K, B, Cs, and Rb) and the mobilization of LREE relative to heavy REE (HREE). The 80°C isotherm is estimated at a depth of 15 km between Blue Moon Seamount and Cerulean Springs. At slab depths of 17 to 24 km, pore waters lack significant Rb and K enrichments relative to seawater, suggesting an upper bound near 150°C. There is an observed enrichment in LREE relative to HREE at Big Blue Seamount (slab depth 25 km) indicating that the décollement at this site is ∼200°C. The relative mobilization of Cs outpaced that of Rb at all seamounts sampled in this survey. On the basis of laboratory experiments, this observation sets an upper limit of ∼350°C at a depth of 30 km below the seafloor.
Keywords: ROV Jason (Remotely Operated Vehicle); ROV Medea (Remotely Operated Vehicle)